Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.2 Exponential Functions and Their Derivatives - 6.2 Exercises - Page 419: 48


$y'=\frac{e^{-2x}(1-2x)}{2\sqrt (1+xe^{-2x})}$

Work Step by Step

$y= \sqrt (1+xe^{-2x})$ Let $t=(1+xe^{-2x})$ This implies $\frac{dt}{dx}=e^{-2x}(1-2x)$ ...(1) Now, $y'=\frac{d}{dt}\sqrt (t)\frac{dt}{dx}$ $=\frac{1}{2\sqrt t}\frac{dt}{dx}$ From equation (1), we get Hence, $y'=\frac{e^{-2x}(1-2x)}{2\sqrt (1+xe^{-2x})}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.